Trauma-exposed young victims: possibilities and constraints for providing trauma support within the investigative interview. Issue 5 (28th May 2017) - Jakobsen, Kristina Kepinska; Langballe, Åse; Schultz, Jon-Håkon
ABSTRACT: For police, the aim of an investigative interview is to obtain a detailed and reliable account from the interviewee while remaining objective and impartial. This study explores the challenges involved in interviewing traumatised young victims and providing trauma support within the legal framework. The study is based on 19 videotaped investigative interviews of highly traumatised young victims of the 2011 Utøya terror attack in Norway and research interviews with the 17 detectives who conducted the police interviews. We analysed the research interviews that comprise the main data using qualitative inductive methods. We used the videotaped investigative interviews as a framework for the research interviews. We identified various types of constraint and support that the detectives perceived and found that objectivity is critical to the interviewers' understanding of their professional role, which results in phase-bound support. At the beginning and end of the interview, they perceive opportunities to be supportive that are in accordance with recommended trauma care. However, the interviewing detectives become more passive when the conversation is about the criminal offence and seem less confident about being supportive. This study provides relevant new insights into how police experience interviewing traumatised young victims.